APLIKASI REINFORCEMENT OLEH GURU MATA PELAJARAN DAN IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING - Wibowo, Agus (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2015)
Abstract: This study originated from problems still lack teachers applying positive reinforcement to behavior that indicated the student in the learning process. The research objective to describe: 1) the level of reinforcement application, 2) application of reinforcement schedules, 3) the types of reinforcement, and 4) granting reinforcement by subject teachers. The study population was all students of class XI SMA Adabiah 2 Padang in the academic year 2012/2013, amounting to 325 students. The samples with Simple Random Sampling technique, and obtained a sample of 176 students.Jenis research is descriptive quantitative research. The study was conducted in April 2013. The research instrument Semantic Differential scale. Analysis of data using mean hypothetic results showed the level of application of the reinforcement of subject teachers in the high category, and interpretation of students to the application of reinforcement schedules, types of reinforcement, and reinforcement by way of provision of subject teachers in the learning process positively.Keywords: reinforcement, guidance, and counseling